(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the prevalence of Hyperprolactinemia in infertile females. Study Design: Observational Descriptive Study Place and Duration of Study: This study was conducted at the Doctor’s Trust Teaching Hospital affiliated with Rai Medical College Sargodha and FertiMed Fertility Centre from February 2019 to February 2020. Materials and Methods: Female patients who presented with primary and secondary infertility among patients who were married and in the reproductive age group (15-49).Total number of the patients in this study was 120.The cut off level of hyperprolactinemia was >25 ng/ml. . The study was not funded. The duration of infertility was not considered. Results: In this study mean age of the patients was 27.86+ with a variation of 6.17.Mean prolactin level was found to be 22.96 with avariation of 9.27ng/ml.The frequency of Hyperprolactinemia was recorded in 54%(n=65).The majority of the patients were mild to moderate hyperprolctinemic. Conclusion: The results of this study advocated the evaluation of infertile female patients with serum prolactin levels, as increased prolactin levels may indicate alteration of hypothalamic pituitary ovarian axis causing reproductive dysfunction.